Structure and activity alteration in adult highland residents' cerebrum: Voxel-based morphometry and amplitude of low-frequency fluctuation study - Zhong, Minzhi; Zeng, Huaqu; Wang, Dongye; Li, Jiesheng; Duan, Xuguang; Li, Yong (Frontiers in Neuroscience, 2022)
Introduction: People living in highland areas may have factors that allow them to adapt to chronic hypoxia, but this physiological mechanism remains unclear. The present study aimed to investigate the brain mechanism in a cohort of adult residents of Tibet, a well-known plateau section in China, by observing differences in brain structure and function in non-plateau populations. Methods: Twenty-seven Tibetan and 27 non-plateau region residents matched in age, sex, and education were enrolled. All participants underwent high-resolution three dimensional T1 weighted imaging (3D-T1WI) and resting-state functional magnetic resonance imaging (rs-fMRI) scans on a 1.5 Tesla MR. Gray matter volumes and regional spontaneous neuronal activity (SNA) were calculated and compared between the two groups. Results: When comparing gray matter in people living in high altitudes to those living in the flatland, the results showed positive activation of gray matter in local brain regions (p < 0.05, false discovery rate (FDR) corrected), in the right postcentral, [automated atomic labelling (aal)], left postcentral (aal), and right lingual (aal) regions. Comparing the people of high altitude vs. flat land in the brain function study (p < 0.05, false discovery rate FDR corrected), positive activation was found in the right superior motor area (aal) and left superior frontal (aal), and negative activation was found in the right precuneus (aal). Conclusion: Larger regional gray matter volumes and higher SNA in high-altitude individuals may represent a compensatory mechanism to adapt to chronic hypoxia.